The influence of gamification learning on students’ critical thinking skills at junior high school - Wardah Wijaya Kurmah; Nana Priajana; Khomarudin Khomarudin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
To overcome the issue of limited student participation in classroom learning, teachers are encouraged to develop and apply innovative teaching strategies. In addition, fostering students’ 21st-century skills is essential, particularly in alignment with the objectives of the Merdeka Curriculum. This study investigates the influence of a gamification learning strategy in fostering students' critical thinking skills in English learning, specifically among eighth-grade students at Junior High School in Indonesia. The research was conducted by first measuring students’ baseline critical thinking skills through a pre-test and then comparing results with a post-test. A quasi-experimental quantitative approach was used, employing a two-group design: the experimental group and the control group. Data analysis was performed using t-test formula. The post-test results indicated that the experimental group scored an average of 85.56, significantly higher than the control group's average of 67.91. The statistical test yielded a sig. (2-tailed) value of 0.001, which is below the 0.05 significance level (p < α), leading to the acceptance of the alternative hypothesis. Therefore, these findings confirm that gamification learning, especially utilizing tools like Quizalize can significantly improve students' engagement and critical thinking in English learning.